Comparison of the effectiveness of cognitive-behavioral therapy, brief intervention and combined intervention on the social support of those who have recovered from Covid-19 - Rahmati, Abbas; Ahmadi, Reza; Mashhadizadeh, Shahram; Ghazanfari, Ahmad (Applied Family Therapy Journal (AFTJ), 2021)
Aim: The present study was conducted with the aim of comparing the effectiveness of cognitive-behavioral therapy, brief intervention and combined intervention on the social support of those who have recovered from Covid-19 in Andimeshk. Methods: The current research method was a semi-experimental type with a pre-test-post-test design with a control group. The research sample includes 80 people who have recovered from the Covid-19 virus, who were covered by comprehensive health service centers in Andimeshk city, who were selected in a purposeful way and randomly assigned to experimental and control groups (20 people in each group). The experimental group underwent cognitive behavioral therapy interventions for 8 sessions of 90 minutes once a week, and the control group did not receive any intervention. Phillips et al.'s social support questionnaire was used to collect data, and covariance analysis was used to test research hypotheses. Results: The results of the research showed that the average scores of social support in cognitive behavioral therapy, brief intervention and combined intervention in the pre-test and post-test stages had a significant difference between the experimental and control groups (P